Improvement of didactics of training wave properties of micro particles of atom origin - Mukashev, K.M.; Aliyeva, M.Ye. (Recent Contributions to Physics, 2017)
The main objective of didactics of training in physics is a support of the maximum accessibility of an entity of any explained physical phenomenon. The proof of this physical phenomenon by means of carrying out an experiment, and also direct participation in statement of an experiment of the trainee is also implementation of the basic principle of training – ensuring presentation of a statement of material. The purpose of the real work is demonstration of the principle of implementation of this provision of didactics of training by means of identification korpuskulyarno – the wave properties inherent in microparticles of an atomic origin. The laboratory stand which doesn’t have an analog in which in an expedited manner the ions of metal moving in electrolyte are passed through a narrow crack has been for this purpose developed. Passing through a crack, they take part in diffraction process. Wave properties of ions are shown in the form of the ionografiya received on the screen which role carries out one of the accelerating electrodes. By the analysis of the received ionografiya pattern, it isn’t difficult to find wavelength of de Broil of microparticles.